2023
DOI: 10.1007/s00066-023-02075-9
|View full text |Cite
|
Sign up to set email alerts
|

Is consolidative thoracic radiotherapy of extensive-stage small cell lung cancer still beneficial in the era of immunotherapy? A retrospective analysis

Abstract: Purpose Extensive-stage small cell lung cancer (ES-SCLC) carries a dismal prognosis. The benefit of consolidative thoracic radiotherapy (TR) after first-line chemoimmunotherapy with PD-L1 inhibitors in this setting remains unclear. As TR can improve overall survival (OS) after conventional chemotherapy, we retrospectively analyzed OS of an inhouse cohort treated either with TR or with chemoimmunotherapy alone. Methods A total of 41 patients treated with ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Only one G3 AE was reported in the TRT group compared to two G3 AEs in the non-TRT group. Moreover, no G4–G5 AEs were observed in the present study, which was similar to other reports ( 13 , 18 ). A good safety profile for TRT in SCLC patients treated with chemoimmunotherapy was also noted.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Only one G3 AE was reported in the TRT group compared to two G3 AEs in the non-TRT group. Moreover, no G4–G5 AEs were observed in the present study, which was similar to other reports ( 13 , 18 ). A good safety profile for TRT in SCLC patients treated with chemoimmunotherapy was also noted.…”
Section: Discussionsupporting
confidence: 93%
“…With regard to toxicity, low AE rates have been reported in prior published retrospective studies ( 13 , 18 , 21 ). Only Peng et al.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…To prevent or attenuate the development of new metachronous BMs, improving extracranial disease control is important. Consolidative thoracic radiotherapy for a partial response after CIT remains controversial [ 1 , 2 , 13 , 19 ]; however, some studies reported positive survival outcomes in patients who received this serial treatment [ 19 ]. Consolidative thoracic radiotherapy with a modest dose (e.g., 30 Gy) and image-guided VMA was a potential treatment option for the regressed thoracic lesions during the maintenance phase with atezolizumab in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…However, the value of cTRT in the immunotherapy era is controversial, as it was not included in the IMPower 133 and CASPIAN trials. But a retrospective study including 41 patients with ES-SCLC, 23 patients received 30Gy/10 fractions cTRT after systemic therapy and 18 patients did not receive cTRT, showed that cTRT significantly improved OS compared with systemic therapy only group (1-year OS 78.6% vs. 39.7%, p=0.019 ( 39 ). Furthermore, several single-center retrospective studies have also demonstrated a survival benefit of cTRT after first-line chemoimmunotherapy ( 40 , 41 ).…”
Section: The Consolidative Thoracic Radiotherapymentioning
confidence: 99%